PERFORMANCE OPTIMIZATION OF SATRESCRIME TO SUPPORT INVESTIGATIONS OF THE CRIMINAL ACTION OF THEFT AT BOYOLALI POLICE - Ikbar Riztki Hibatullah (Indonesian Journal of Police Studies, 2022)
According to data from the last three years in Boyolali Police, the theft rate is relatively high and tends to increase. Additionally, crime clearance and crime total are not balanced, despite total crime being significantly higher than crime clearance. This condition motivated the author to investigate the performance of the Satreskrim Polres Boyolali. This research used qualitative research methods. The focus of the research was the the performance of the Satreskrim Polres Boyolali conducted the investigations criminal acts of theft. The researcher used data collection techniques with interviews, document studies, and observations. Engineering triangulation and source triangulation were used to validate the data. The results showed that there are still many Satreskrim investigators who have not engaged in in education and the development of specialties of reserse and criminal functions. There was also the funding, which was not in sync with the DIPA assimilation financing. Furthermore, buildings and infrastructure that do not support operations have been uncovered as a result of destruction and a lack of managerial to members of the leadership. The performance of Satreskrim has not improved much. According to Perkap No. 1 of 2019, a police operation plan is considered successful if it has a 60% success rate. However, according to field survey, Satreskrim Polres Boyolali's effectiveness rate was only 31%. Besides that, factors that affect both internally and externally, such as member ability, funding discrepancy with the distribution, lack of managerial to members, and people who still do not understand the importance of maintaining crime scene conditions, were also the cause of the non-optimal performance of Satreskirm